Changing Online Shopping Experiences: Investigating Quality of Augmented Reality (AR) Experience on Behavioral Intentions using S-O-R Theory - Raja Zohaib Ghafoor; Saddam Hussain; Ayaz Ahmad (International Journal of Business and Economic Affairs, 2023)
It is an Augmented Reality (AR) experience-induced study investigating a framework centered on the Stimulus-Organism-Response (S-O-R) theory comprising the quality of AR experience, perceived value, Augmented Reality Information Privacy Concern (ARIPC), and behavioral intentions in online shopping customers. The data was collected from Pakistani customers through a self-administered questionnaire after they experienced the AR app. In total, 1457 responses were examined using the Partial Least Square method in SmartPLS4. The findings reveal that the quality of AR experience, ARIPC, and perceived value are the key determinants of behavioral intentions in online shopping. Additionally, this study shows that ARIPC and perceived value fully mediate the relationship between the quality of AR experience and behavioral intentions. Moreover, a serial mediation also exists between the quality of AR experience and behavioral intentions through ARIPC and perceived value in the model. These findings offer a better insight for academicians and practitioners of consumer behavior in online shopping using immersive technology like AR. No study has investigated the online shopping behavior of Pakistani customers using the quality of AR experience in the footwear industry. Moreover, ARIPC has been empirically tested first time in this study showing that the benefits of using AR overcome AR-related privacy concerns.